Jobs for Brazil’s Poor : Social Protection Programs and Labor Supply Impacts on the Poor in Brazil - Robalino, David; de la Brière, Bénédicte; Lindert, Kathy (World Bank, Washington, DC, 2012)
The World Bank is carrying out a program of Analytic and Advisory Activities (the Labor AAA) focused on the interface between social protection programs and labor supply and productivity. This focus relates to the debates in Brazil surrounding the issue of helping transfer beneficiaries graduate from poverty and from dependence on transfer incomes. The AAA is structured along two pillars. Pillar I addresses questions related to the impacts of explicit and implicit public transfers on labor supply and savings decisions. In particular, what is the effect of public transfers such as Bolsa Familia and those related to the social insurance system (pensions and unemployment) on work incentives, early entry and retirement, sector choice, and ultimately, public expenditures, human capital accumulation and growth. Pillar II focuses on program design and evaluation. The and goal is to identify how the portfolio of transfer and active labor market programs can be optimized to enhance the employability of the poor, help promote their graduation from poverty, and, ultimately, from dependence on transfer income. In addition, the Labor AAA includes a component to assess public perceptions about Social Protection programs. The Labor AAA is a living program that seeks to respond to questions posed by Brazilian policy-makers as they strengthen the education-social protection-labor market nexus. This approach is helping convene the different stakeholders at the federal level by bringing evidence and policy analysis to the debates.